Tephrostratigraphy of Pleistocene-Holocene deposits from the Detroit Rise eastern slope (northwestern Pacific) - Derkachev, Alexander; Gorbarenko, Sergey; Portnyagin, Maxim; Zhong, Yi; Nikolaeva, Nataliya; Shi, Xuefa; Liu, Yanguang (Frontiers in Earth Science, 2023)
This paper presents new data on the composition of volcanic ash (tephra) found in the Pleistocene deposits of the northwestern Pacific. The main goal of the study was to establish the spatial and temporal distribution of pyroclastic material from strong explosive eruptions of the volcanoes of Kamchatka, the Kuril, and Aleutian Islands to create a generalized tephrochronological model and reveal patterns of explosive activity in this region. On the eastern slope of the Detroit Rise (in the northwestern part of the Imperial Ridge), eleven layers and lenses of tephras aged from 28 to 245 ka, which were previously unknown, were studied. Their stratigraphic position and age were determined based on age models developed by the authors. Based on the geochemical characteristics of volcanic glass (determined using an electron microprobe), seven layers were correlated with tephra from several cores in the northwestern Pacific and the Bering Sea. The obtained results supplement the information on large explosive eruptions of volcanoes in the region and their activation periods to assess the climatic changes caused by these eruptions; they also allow the development of a generalized tephrochronological model of Quaternary deposits, which is necessary for stratigraphic correlation, and of paleooceanological and paleogeographic reconstructions.